Adherence and HIV RNA Suppression in the Current Era of Highly Active Antiretroviral Therapy. (1st August 2015) - Viswanathan, Shilpa; Justice, Amy C.; Alexander, G. Caleb; Brown, Todd T.; Gandhi, Neel R.; McNicholl, Ian R.; Rimland, David; Rodriguez-Barradas, Maria C.; Jacobson, Lisa P.
Abstract : Background: We examined trends in adherence to highly active antiretroviral therapy (HAART) and HIV RNA suppression and estimated the minimum cutoff of adherence to newer HAART formulations needed for HIV RNA suppression by regimen type. Methods: We used Veterans Affairs pharmacy dispensing data from the Veterans Aging Cohort Study Virtual Cohort between October 2000 and September 2010 and defined adherence as the duration of time the patient had the medications available, relative to the total number of days between refills for all antiretrovirals in a year. Temporal trends in adherence and viral load suppression were examined by the patient's most frequently used HAART regimen in the year. The minimum needed adherence was defined as the level at which the odds of suppression was not significantly different than that observed with ≥95% adherence using repeated-measures logistic regression. Results: A total of 21, 865 HAART users contributed 82, 217 person-years of follow-up. There was a significant increase ( P trend < 0.001) in the proportion virally suppressed even among those with <95% adherence (2001: 38% to 2010: 84%), and the trend was similar when restricting to their first HAART regimen. For nonnucleoside reverse transcriptase inhibitor multi-pill users, the odds of suppression did not differ for 85%–89% adherence compared to those with ≥95% adherence [odds ratios: 0.82 (0.64–1.04)], but for protease inhibitor users, the odds of suppression significantly differed if adherence levels were <95% compared to ≥95% adherence. Conclusions: Although all HIV-infected persons should be instructed to achieve perfect adherence, concerns of slightly lower adherence should not hinder prescribing new HAART regimens early in HIV infection. Abstract : Supplemental Digital Content is Available in the Text.